Exploring Coffee Tourism: Its Impact on Coffee Bean Sales in West Java, Indonesia - Suratman, Dadang; Rumayar, Cristian Helmy; Wijaya, Cecep Tatang; ., Wahyudin; Yuliawati, Ayu Krishna; Hadian, Mohamad Sapari Dwi (Journal of Ecohumanism, 2024)
This study explores the impact of coffee tourism on coffee bean sales in West Java, Indonesia, focusing on how tourism supports the marketing of local products. Data was collected through surveys involving coffee tourists, café owners, and farmers in the Bandung, Pangalengan, and Ciwidey regions. Results indicate that coffee tourism significantly increases coffee bean sales, with 68% of respondents purchasing coffee during tourism activities. Furthermore, 93% believe local coffee is of high quality, and 68% make repeat purchases. Coffee tourism also enhances public awareness of local brands, with 100% of respondents becoming more familiar with local products after visits. However, local coffee farmers face challenges such as limited production capacity to meet growing demand and market price fluctuations. The study suggests integrating tourism with marketing strategies to boost coffee farmers' economic prospects by improving market access and promoting products more effectively. Additionally, it emphasizes the need for government and private sector support to develop infrastructure and marketing efforts that align with growing coffee tourism trends. Local farmers and producers can tap into a broader consumer base by leveraging coffee tourism, promoting sustainable economic growth in the coffee sector.